(untitled) (Research, Society and Development, 2022)
Objective: to evaluate the students’ perception of the problems used in the tutorial axis of the Physiotherapy course at the Universidade do Estado do Pará. Method: This is a descriptive study, with a quantitative approach, carried out through a questionnaire applied to Physiotherapy students who experienced PBL. The research took place at the University of the State of Pará - UEPA. The results obtained in the questionnaire were digitized, tabulated and consolidated in the Microsoft Excel program, where frequency tables of the categorical variables (answers to the questions) were made, with the values of absolute frequency (n) and percentage (%). Subsequently, the analysis of each statement (Q) was performed in relation to the averages obtained, most of the statements should reach an average equal to or above 80% (positive averages). Results and discussion: the general percentage of agreement of the participants was of 86%, referring to the values of CT and CP, demonstrating that the level of satisfaction of the students is satisfactory for the structure of the problems. Final considerations: The participants of this study demonstrated that the problems of the tutoring axis are being formulated according to what is recommended in the literature, demonstrating that the PBL methodology, in the Physiotherapy course at UEPA, reaches a satisfactory level.